4M2006 : Second International Conference on Multi-Material Micro Manufacture : 20-22 September 2006, Grenoble, France - Menz, W. (Wolfgang); Dimov, S. S., 1959-; Fillon, Bertrand (Elsevier, 2006)
This work covers the latest state-of-the-art research results from leading European researchers in advanced micro technologies for batch processing of metals, polymers, and ceramics, and the development of new production platforms for micro systems-based products. These contributions are from leading authors at a platform endorsed and funded by the European Union R & D community, as well as leading universities, and independent research and corporate organizations. This comprehensive collection of indexed and peer reviewed articles contains a CD with search functionality. * Contains authoritative papers that reflect the latest developments in micro technologies and micro systems-based products * Includes a user-friendly CD Rom with search functionality.